Pre-antigenic regulatory signals in osteoarthritis: modulators of dendritic cell activation and joint immune balance - Liang, Jiabao; Jackson, Andrew Mark (Frontiers in Immunology, 2026)
Osteoarthritis (OA) is now recognized as an immune-metabolic disorder rather than a simple wear-and-tear disease. Dendritic cells (DCs) in the synovium and subchondral bone link mechanical, biochemical, and metabolic stress to immune imbalance. In the early stage of immune activation, pre-antigenic regulatory signals act before classical antigen presentation and influence how DCs shape joint immunity. Increased extracellular matrix (ECM) stiffness activates the Integrin-FAK-NF-κB pathway, driving inflammatory or exhausted DC states. ECM fragments and damage-associated molecular patterns (DAMPs) stimulate pattern recognition receptors (PRRs), inducing cytokines that sustain chronic inflammation. Hypoxia, lactate, and oxidative stress reprogram DC metabolism, suppress IL-12, and promote Th17 responses. Targeting these upstream factors offers new therapeutic opportunities. Strategies that modify matrix stiffness, block DAMP-mediated signaling, or restore metabolic balance can help reset DC function and preserve joint homeostasis. Emerging biomaterial-based approaches further provide a foundation for immune-restorative and regenerative therapies. In the future, integrating DC-modulatory materials with personalized immune profiling may enable precise immuno-regenerative treatments for OA, representing a shift from symptom relief to immune-guided cartilage repair.